Additives for construction market from zinc metallurgy tailing - Saulo De Rezende; Caio Moreira; Nelly Ruíz (Instituto de Ingenieros de Minas del Peru, 2023)
The present project sought alternatives for this material through the Mining Lab Beginnings program, which was developed by Nexa in partnership with Escalab to find solutions for the company's highly complex challenges. Through the program, several solutions were evaluated, with additives for the construction market being the most prominent. Tests were conducted to confirm the efficiency of jarosite in the mixture that composes this material. With successful laboratory tests, the technology was tested on an industrial scale, where it also demonstrated its technical and economic viability. The project is now moving into the operational phase, demonstrating that circular economy is the best solution for disposed tailings.